Numerical investigation of aerodynamic parameters across NaCa6415 airfoil. (2021) - Ali, Rashid; Akhtar, Shadab; Farhan, Mohd; Alam, Firdous
Abstract: In the current study the effects of air velocity and angle of attack on aerodynamic parameters across NACA6415 airfoil are investigated. The air velocity is chosen as 15 m/s, 20 m/s, 25 m/s, 30 m/s, and 35 m/s. The angle of attack is in the ranges [-10 o to 20°]. The flow field is considered as viscous, unsteady, compressible and turbulent. To solve the continuity and momentum equations the CFD solver ANSYS FLUENT is used. Realizable K-epsilon model is used to simulate mean flow characteristics in turbulence conditions. Triangular structural mesh is generated having 28, 722 element. It is observed from the time histories of lift, drag and moment coefficients that the transition time is less and the solution is converge within 50 s, the solution becomes stable and remains stable at higher time levels. It is found that the coefficient of lift increases with increase in angle of attack, maximum lift coefficient is found to be 1.286 at V = 25 m/s and α = 10°. The drag coefficient is observed maximum 0.269 at V = 15 m/s and α = 20°. It is also observed that at air velocity of V = 15 m/s, the drag coefficient decreases with increase in angle of attack and reaches to its minimum at α = 0°, and increases with increase in angle of attack to a maximum value at α = 20°. It is found that the moment coefficient followed the same trend as followed by the lift coefficient. Maximum moment coefficient 2.546 is found to occur at V = 25 m/s and α = 10°. It is found that the ration of Cl / Cd is increased for V = 25 m/s and nearly negligible for V = 20 m/s and decreases with increase in angle of attack for V = 30 m/s& 35 m/s, respectively. Cl / Cd ratio at V = 15 m/s increases with increasing angle of attack reaches to a maximum value and decrease thereafter with increase in angle of attack. Maximum Cl /Cd ratio is found to be 21.666 at V = 35 m/s and α = 0°.